Combined transcriptome and metabolome analysis identifies defence responses in spider mite-infested pepper (Capsicum annuum). (26th September 2019) - Zhang, Yuanyuan; Bouwmeester, Harro J; Kappers, Iris F
Abstract: Plants regulate responses towards herbivory through fine-tuning of defence-related hormone production, expression of defence genes, and production of secondary metabolites. Jasmonic acid (JA) plays a key role in plant–herbivorous arthropod interactions. To understand how pepper (Capsicum annuum) responds to herbivory, leaf transcriptomes and metabolomes of two genotypes different in their susceptibility to spider mites were studied. Mites induced both JA and salicylic acid (SA) signalling. However, mite infestation and exogenous JA resulted in distinct transcriptome profiles. Compared with JA, mites induced fewer differentially expressed genes involved in metabolic processes (except for genes involved in the phenylpropanoid pathway) and lipid metabolic processes. Furthermore, pathogen-related defence responses including WRKY transcription factors were more strongly induced upon mite infestation, probably as a result of induced SA signalling. Untargeted analysis of secondary metabolites confirmed that JA treatment induced larger changes in metabolism than spider mite infestation, resulting in higher terpenoid and flavonoid production. The more resistant genotype exhibited a larger increase in endogenous JA and volatile and non-volatile secondary metabolites upon infestation, which could explain its stronger defence. Reasoning that in JA–SA antagonizing crosstalk, SA defences are prioritized over JA defences, we hypothesize that lack of SA-mediated repression of JA-induced defences could result in gain of resistance towards spider mites in pepper. Abstract : Lack of SA-mediated repression of JA-induced specialized metabolites results in gain of resistance towards spider mites in pepper